Student progressive-metacognitive video analysis effects on systemic regulation and learning in physics - Monterola, Sheryl Lyn C.
" The study investigated the effects of Student Progressive-Metacognitive Video Analysis (SPMVA) and Progressive- Metacognitive Analysis Teaching Approach (PMTA) on systemic regulation and learning in secondary physics, specifically on social and self-regulation skills, group task performance, and physics achievement. In addition, the study probed the extent to which metacognitive knowledge and students’ attitude towards group learning moderated the effects of progressive-metacognitive teaching approaches (SPMVA and PMTA) on different student outcomes. Lastly, it investigated the relationship between group and individual learning outcomes. The study utilized a three-group pretest-posttest quasi-experimental design. Ninety seven (97) fourth-year high school students enrolled in a laboratory high school participated in the study. Three intact classes were randomly assigned to three teaching approach groups—Student Progressive-Metacognitive Video Analysis (SPMVA), Progressive-Metacognitive Analysis (PMTA), and Non-Metacognitive (NMTA). The researcher taught all three classes using parallel lesson plans, with only the metacognitive analysis as differentiating intervention. The researcher-made instruments in the study were: the Metacognitive Physics Knowledge Inventory (MPKI), the Attitude towards Group Learning Scale (AGLS), the Social Regulation in Physics Group Work Scale (SoRS), the Self-Regulation Skills in Physics Scale (SeRP), the Group Task Performance Assessment (GTPA), and the Physics Achievement Test (PAT). The instruments were validated by a panel of experts and were pilot tested. The instruments were administered both as pretest and posttest. One-way analysis of variance (ANOVA) was used to compare mean scores/ratings of the three classes in pre- and post-assessment instruments. Multivariate Analysis of Variance (MANOVA) was conducted to investigate differences among the three teaching approach groups on a combination of learning outcomes..." --